Scoring Transcendence : Contemporary Film Music as Religious Experience - Callaway, Kutter, 1979- (Book collections on Project MUSE., 2013)
Films are the lingua franca of western culture; for decades they have provided viewers with a universal way of understanding the human experience. And film music, the author demonstrates, has such a profound effect on the human spirit that it demands theological reflection. By engaging scores from the last decade of popular cinema, the author reveals how a musically aware approach to film can yield novel insights into the presence and activity of God in contemporary culture. And, through conversations with these films and their filmmakers, viewers can gain a new understanding of how God may be speaking to modern society through film and its transcendent melodies.